2018
DOI: 10.1016/j.jvs.2017.07.124
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hybrid procedure for type B aortic dissection with an aberrant right subclavian artery

Abstract: Our limited experience demonstrates that a hybrid procedure is a viable and relatively safe treatment strategy for patients with TBAD and an ARSA. A larger series of cases with a longer follow-up is needed to substantiate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…18 An extra-anatomic bypass hybrid procedure or chimney stent was performed in cases with an insufficient aortic arch landing zone. 19,20…”
Section: Description Of Proceduresmentioning
confidence: 99%
“…18 An extra-anatomic bypass hybrid procedure or chimney stent was performed in cases with an insufficient aortic arch landing zone. 19,20…”
Section: Description Of Proceduresmentioning
confidence: 99%
“…Several surgical procedures have been reported to treat patients with acute type B aortic syndrome and ARSA, including replacement of the descending aorta, total arch replacement plus stent elephant trunk, only the stented elephant trunk method, hybrid technique, and TEVAR. 7,12 The descending aorta replacement for treating TBAD and ARSA was first reported by DeBakey in 1955. 13 It was not until 1973 that Syme et al carried out the second descending aorta replacement for managing this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the rarity of coexistence of ARSA and acute type B aortic syndrome, only a few cases have been reported on the treatment methods, mainly including open surgery, 5,6 and hybrid operation. [7][8][9] Over the past 20 years, thoracic endovascular aortic repair (TEVAR) has been developed rapidly and becomes more accepted in the treatment of acute type B aortic syndrome for its lower mortality and morbidity. However, the existence of ARSA brings additional challenges for TEVAR in repairing the diseased aorta due to preserving the blood supply from the ARSA to brain and right upper extremity.…”
Section: Introductionmentioning
confidence: 99%
“…Successful repair of Kommerell diverticulum using alternative endovascular and hybrid techniques has been reported [13,19,20], with 1 early death (2.6%) reported in a review of 38 cases of hybrid repair procedures [6]. Van Bogerijen and colleagues [21] reported that the evolution of endovascular repair did not affect late outcomes in their 3.0 AE 3.4 years of follow-up.…”
Section: Commentmentioning
confidence: 99%